2000
DOI: 10.1093/nar/28.18.3504
|View full text |Cite
|
Sign up to set email alerts
|

H-NS mediated compaction of DNA visualised by atomic force microscopy

Abstract: The Escherichia coli H-NS protein is a nucleoid-associated protein involved in gene regulation and DNA compaction. To get more insight into the mechanism of DNA compaction we applied atomic force microscopy (AFM) to study the structure of H-NS-DNA complexes. On circular DNA molecules two different levels of H-NS induced condensation were observed. H-NS induced lateral condensation of large regions of the plasmid. In addition, large globular structures were identified that incorporated a considerable amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
237
2
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(257 citation statements)
references
References 33 publications
(33 reference statements)
16
237
2
2
Order By: Relevance
“…This conclusion is in good agreement with recent microscopic studies, which showed the formation of filamentous structures when visualizing H-NS⅐DNA complexes (41,42). These filaments are constituted by large tracts with two regions of double-stranded DNA held close together (41).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This conclusion is in good agreement with recent microscopic studies, which showed the formation of filamentous structures when visualizing H-NS⅐DNA complexes (41,42). These filaments are constituted by large tracts with two regions of double-stranded DNA held close together (41).…”
Section: Discussionsupporting
confidence: 92%
“…This conclusion is in good agreement with recent microscopic studies, which showed the formation of filamentous structures when visualizing H-NS⅐DNA complexes (41,42). These filaments are constituted by large tracts with two regions of double-stranded DNA held close together (41). It was proposed, from their observation, that the binding of H-NS to DNA would occur through a nucleation step followed by a zipper-like propagation along the DNA (42).…”
Section: Discussionsupporting
confidence: 90%
“…H-NS is responsible for binding and repressing >400 genes in Salmonella (4, 7) and in Escherichia coli (8,9), many of which are DNA sequences obtained through horizontal gene transfer and involved in adaptive stress responses and virulence (10). Numerous phenotypes associated with hns mutations have been described, and the effects of H-NS on gene expression are largely inhibitory (2,11), which is partially explained by the ability of H-NS to bridge adjacent helices of DNA (12,13), causing either the trapping or the occlusion of RNA polymerase in the promoter regions (2,14). H-NS homologs are widespread in the Gram-negative α-, β-, and γ-proteobacteria but have not been identified in Gram-positive bacteria or in any other groups of bacteria, leaving it unclear as to how these bacterial species regulate the genes that they obtain through genetic exchange.…”
Section: H-ns | Virulencementioning
confidence: 99%
“…H-NS is an abundant bacterial NAP, but, unlike HU, which is believed to constrain a toroidal DNA structure analogous to that in a nucleosome (Rouvière-Yaniv et al 1979;Guo and Adhya 2007), H-NS complexes can bridge two DNA duplexes (Dame et al 2000) and concomitantly stabilize the plectonemic form of negatively supercoiled DNA (Schneider et al 2001). In vivo, two principal functions have been ascribed to H-NS: as a repressor of certain genes and gene clusters located in A/T-rich regions of the genome (Navarre et al 2006;Ouafa et al 2012), and as a domainin, assumed to function by stabilizing barriers between distinct topological domains (Hardy and Cozzarelli 2005).…”
Section: H-ns Nucleoprotein Complexesmentioning
confidence: 99%